2012
DOI: 10.1258/ar.2012.120238
|View full text |Cite
|
Sign up to set email alerts
|

Breast compression in mammography: pressure distribution patterns

Abstract: The distribution of pressure differed greatly between breasts. In a large proportion of breasts the compression plate did not provide optimal compression of the breast, the compression force being absorbed in juxtathoracic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 20 publications
4
58
1
Order By: Relevance
“…There are several factors that might affect the applied compression force in mammography; the female, [18][19][20] the equipment 21,22 and the radiographer. [8][9][10][11]22,23 Factors related to the screened female include differences in breast volume, 18 breast stiffness and compressibility 19,20 and acceptance of pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several factors that might affect the applied compression force in mammography; the female, [18][19][20] the equipment 21,22 and the radiographer. [8][9][10][11]22,23 Factors related to the screened female include differences in breast volume, 18 breast stiffness and compressibility 19,20 and acceptance of pain.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11]22,23 Factors related to the screened female include differences in breast volume, 18 breast stiffness and compressibility 19,20 and acceptance of pain. Characteristics of the breast compression paddle, 24 positioning of the compression paddle, 22,23 positioning of the detector plate 21 and use of automated compression force methods 22 are factors related to the equipment. The positioning of the breast compression paddle and detector plate will affect how the pressure from breast compression is distributed across the breast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Studies have shown that using too little compression can result in blurring; also, one study has demonstrated that compression force is not evenly distributed across the breast, and for the mediolateral oblique view, a lot of compression is lost in the pectoral muscle leading to undercompression in the rest of the breast. 4 Human perception of blurring could be affected by the distribution of contrast across different spatial frequencies. For instance, if the high spatial frequencies are filtered by a low-pass spatial filter, the image will appear blurred, while the image will appear sharp if low spatial frequencies are filtered by a high-pass spatial filter.…”
mentioning
confidence: 99%
“…Recent publications point out that controlling pressure can be beneficial in terms of reproducibility, pain, radiation dose, image quality, and detectability of breast cancer. [1][2][3][4][5][6][7][8][9][10][11][12][13] For many years, breast compression has been susceptible to subjectivity and thus large variations in the applied pressure. With mammography systems indicating only the force applied by the paddle, but not the area over which the force is distributed, 14 the exerted pressure (force divided by area) could only be estimated based on subjective cues, such as skin tautness or the patient's perceived pain experience.…”
Section: Introductionmentioning
confidence: 99%